A qualitative assessment of the sexual-health education, training and service needs of young adults in Tehran - Narges Sheikhansari; Charles Abraham; Sarah Denford; Mehrdad Eftekhar (BMC, 2021)
Abstract Background Sexual Health and Relationships Education (SHRE) provides individuals with knowledge and skills to manage risky behaviors and take informed decisions to protect themselves against STIs, and unintended pregnancy. Only minimal SHRE is provided in Iranian schools and universities and previous research has highlighted needs and demands for improved SHRE and sexual services in Iran. This study explored young, Iranian adults' experience of, and need for sexual health education, sexual skills training and sexual healthcare services, as well their views on how to augment and improve existing provision. Design and methods Semi-structured interviews were conducted with a sample of 25 young adults who lived in Tehran, Iran and had volunteered to participate in the study. Transcripts were analyzed using thematic analysis. Results Participants explained their needs and demands for sexual health education and sexual healthcare. They unanimously expressed their dissatisfaction with available SHRE and sexual health care provision. They highlighted barriers to gaining sexual health information and seeking advice and healthcare, including a lack of reliable resources, taboo and cultural barriers, lack of trust and protected confidentiality. This has resulted in ambiguities and misconceptions, including those regarding the cause and transmission of STIs and correct use of contraceptives. Participants recommended improvements, including holding mixed-gender extracurricular workshops with a comprehensive approach to sexual health and relationships education. Conclusions There is a clear need and demand for provision of relevant and reliable sexual health and relationships education for young adults in Tehran. This should be addressed to empower young people to make informed choices and avoid risky sexual behavior.